Our Quaker Friends of ye olden time: being in part a transcript of the minute books of Cedar Creek meeting, Hanover County, and the South River meeting, Campbell County, Va - Bell, James Pinkney Pleasant (J. P. Bell Co., 1905)
Births and deaths -- Marriages -- Removals -- Disownments -- Confession and condemnation -- Appendix 1: Historical sketch -- Appendix 2: Doctrines held by Society of Friends -- Appendix 3. Declaration of faith -- Appendix 4: Prominent families -- Appendix 5: Colonial church ; One hundred years ago (a poem) -- Appendix 6: The diary of John B. Crenshaw.